1997
DOI: 10.1097/00007890-199701150-00027
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Pigs Expressing Human Cd59 and Decay-Accelerating Factor Produce an Intrinsic Barrier to Complement-Mediated Damage1

Abstract: We characterize a line of transgenic pigs that express the human complement-regulatory proteins human CD59 and human decay-accelerating factor. These genes, under the control of heterologous promoters, are expressed in a variety of organs, including the vasculature of the heart, kidney, and liver. We demonstrate that moderate levels of these gene products are sufficient to protect peripheral blood cells from human or baboon complement. Using pig to baboon heterotopic heart transplants, we show that expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
133
1
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(140 citation statements)
references
References 26 publications
5
133
1
1
Order By: Relevance
“…The first form of xenorejection, hyperacute rejection, occurs upon reperfusion of xenografts by the recipient blood because of binding of natural xenoantibodies to endothelial cells of the graft and activation of the complement system (1,2). This can be overcome by interfering with the complement system, e.g., by using genetically modified donors (3). When hyperacute rejection is averted, acute vascular rejection (AVR) 3 and T cell-mediated cellular rejection are the next major hurdles to the clinical application of xenotransplantation.…”
Section: Pathogenesis Of Autoimmunity After Xenogeneic Thymus Transplmentioning
confidence: 99%
“…The first form of xenorejection, hyperacute rejection, occurs upon reperfusion of xenografts by the recipient blood because of binding of natural xenoantibodies to endothelial cells of the graft and activation of the complement system (1,2). This can be overcome by interfering with the complement system, e.g., by using genetically modified donors (3). When hyperacute rejection is averted, acute vascular rejection (AVR) 3 and T cell-mediated cellular rejection are the next major hurdles to the clinical application of xenotransplantation.…”
Section: Pathogenesis Of Autoimmunity After Xenogeneic Thymus Transplmentioning
confidence: 99%
“…By forming pores in the cell membrane, C5b-9 causes cell death in part through unregulated Ca 2ϩ influx (21,22). However, OLG, like other nucleated cells, survive limited complement attack through protection by complement-inhibitory proteins and by elimination of membranes carrying C5b-9 complexes (23)(24)(25)(26)(27)(28). We recently demonstrated that sublytic doses of C5b-9 inhibit the caspase-3-dependent OLG apoptosis induced in vitro by serum deprivation or TNF-␣ (29).…”
Section: O Ligodendrocytes (Olg)mentioning
confidence: 99%
“…Many porcine cell types and all vascularized organs transplanted into primate models are rejected by both humoral and cellular mechanisms (5,6). Major advances have been made in abrogating the humoral component that leads to hyperacute rejection, mainly through complement inhibition (7)(8)(9)(10). However, even in the presence of complement inhibitors and systemic immunosuppression, xenografts are rejected due to delayed xenograft rejection (DXR) 4 (3,6,(11)(12)(13)(14).…”
mentioning
confidence: 99%